Influence of Ground Coal Bottom Ash on the Properties of Concrete - Mangi, Sajjad Ali; Mohd Haziman, Wan Ibrahim; Norwati, Jamaluddin; Shahiron, Shahidan; Mohd Fadzil, Arshad; Memon, Sheeraz Ahmed; Putra Jaya, Ramadhansyah; Mudjanarko, Sri Wiwoho; Setiawan, Muhammad Ikhsan (UTHM, 2018)
The coal based thermal power plant in Malaysia produces annually around 1.7 million tons of coal bottom ash (CBA) as a discarded material which poses great environmental problems. Hence, the objective of this study is to utilize ground CBA as a supplementary cementing material in concrete. The oven dried original CBA was grinded for 20hours to achieve required fineness. The mixture of concrete was prepared with CBA proportion of 10, 20 and 30% by weight of cement. For the evaluation of density, water absorption, compressive and tensile strength of concrete, 48 specimens were cast. The workability of fresh mix concrete was also evaluated, and it was found to be decreased as the quantity of CBA increased in the mixture. However, the compressive and splitting tensile strength of concrete was also reduced with the addition of ground CBA but with 10% replacement has attended the targeted compressive strength at the age of 28days. Besides that, it was also observed that the influence of CBA on concrete is obvious in density as well as in water absorption. The density of concrete gradually decreased due to addition of ground CBA, concrete containing 10% ground CBA was likely to be similar to that of control mix and the opposite performance was noticed in water absorption. Hence, experimental findings of this study indicated potentiality of ground CBA as supplementary cementing material in concrete construction which will reduces the environmental concern.